Traditional Society Assessed From Legal Sociology - Bagus Kurnianto (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
Law as a cultural product has always existed in every society, both traditional and primitive societies. Law develops and grows in society itself. Laws are not formed, but laws are found. Therefore, every society has laws that have lived and grown together with the growth and development of society. This law is known as the living law. However, as modern countries grow and develop, the living law tends to be eliminated and replaced with positive law. The living law is not considered law. Even in the civil law tradition, positive law (law) in Indonesia is the main source of law, but in reality the living law is still recognized to some extent. So that the judge who has the authority to decide a case, it is fitting to explore the sense of law that grows and develops in communities, especially indigenous peoples who have already used customary law in society.